MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN DI JURUSAN KEBIDANAN POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PONTIANAK - Rosita, Desy; Wahyudi, Wahyudi; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractManagement of educators and education is a process of planning, organizing, Actuating and Controlling the lecturer and the structure and all components contained in the institution or educational institution to achieve the objectives tha have been determined effectively and efficiently trough human resources.The purpose of study was to obtain descriptive information about the Planning, Organizing, Actuating and Controlling.With a qualitative approach and case study, this thesis prepared using primary data and secondary data trough interviews, observation, and documentation. Data analysis using data reduction, data presentation and conclution.The study found that the management Educators and Education Personnel concultion. 1)This research finds the planning of educatorsand education personnel in the department of midwifery Poltekkes Kemenkes Pontianak through the process of mapping, analyzing the needs, proposing the forwardto Derectorate for selection, for recruitment of non-civil servants referring to the act and government regulation related to officer. 2) the organization of educatorsand education personnel in the department of midwifery Poltekkes Kemenkes Pontianak implemented based on the organizational structure Poltekkes and organizational structuremidwifery department. 3)Actuating of educatorsand education personnel in the department of midwifery Poltekkesgiven by the head of study programdirectly responsible chairmanof the department through individual group meetins.4) Controllingof educatorsand education personnel in the department of midwifery Poltekkes Kemenkes Pontianak is conducted by the head of the study program directlyresponsible to the head of department, performance appraisal is measured by employee performace target wich effects the benefits received. Keyword :Management of Educators and Education Personnel